Résurgence institutionnelle et avenir de la géographie politique en France depuis les années 1970 - André-Louis Sanguin (L'Espace Politique)
This paper recounts the history of the Commission on Political Geography (French National Committee for Geography) since its founding in 1984 within the more general framework regarding the political geography’s development after its reappearance in France during the 70s. It stresses on the context of a revival as well as the conceptual and subject innovations which were pushed by the Commission. It analyses too the parallel and independent route taken by the Lacoste’s geopolitics and the review Hérodote. Beyond the political geography’s institutionalization in France, this paper concludes on the new post-2010 problems and prospects which affect this area of the geographical science.